(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Pakistan ranks among the South Asian nations with the highest rate of maternal mortality, especially in the rural areas. These rural women face maternal complications, often worsened by delayed care; hence, understanding their nature and prevalence is vital for targeted interventions. Objectives: To determine the prevalence of self reported maternal complications among rural women and to prioritize targeted interventions to minimize the prevalence of maternal complications. Material and method: Descriptive cross-sectional study was conducted at Gynecology and Obstetrics Outpatient Department (OPD) healthcare centers in the Mirpurkhas district targeting rural populations. Data was collected through a questionnaire, which was further divided in sub section from 271 participants. Socio-demographic characteristics, personal information and self-reported complications mothers were analyzed. Results: Study showed that most of women are from rural areas and the mean age of participants was 28 with standard deviation + of 05.63% of participants were illiterate, bleeding was found in 60.1% of participants and 56.5% of participants had infection. Others complications such as hypertension, preterm labor and placental issues also found in low majority in current study. CONCLUSION: The prevalence of bleeding during and after pregnancy among rural women was very high. The study also highlighted that the infection and hypertension as self-reported complication.